Determination of Fructans in Infant Formula and Adult/Pediatric Nutritional Formula by Anion-Exchange Chromatography with Pulsed Amperometric Detection after Enzymatic Treatment: Collaborative Study, Final Action 2016.14. (8th May 2020) - Spichtig, Véronique; Austin, Sean; Brunt, Kommer; Van Soest, Jeroen; Sanders, Peter
Abstract: Background: Fructans are added to infant formula and adult nutritionals for their prebiotic effect. A method (AOAC 2016.14 ) was developed for their analysis which has already demonstrated excellent performance during single laboratory validation. Objective: To determine repeatability and reproducibility of the method through a collaborative study. Methods: Fourteen laboratories from 11 different countries enrolled for the study. Participants analyzed a practice sample, then 8 formula or adult nutritionals in blind duplicate. Results and any method modifications were reported to the study director. Results: Twelve laboratories provided results on time for reporting. Precision results for five samples met the requirements of the Standard Method Performance Requirements (SMPR 2014.002), with RSDr ranging from 3.60 to 4.25% and RSDR ranging from 5.90 to 11.7%. The practice sample also met the requirements of SMPR 2014.002, with RSDr and RSDR of 2.53% and 6.70% respectively. Precision results for three test samples did not fully meet the SMPR, with RSDr ranging from 2.27 to 7.65% and RSDR ranging from 12.8 to 15.1%. After review, the AOAC Stakeholder Panel for Infant Formula and Adult Nutritional Expert Review Panel (SPIFAN ERP) concluded that the data presented mostly met the SMPR and hence recommended that the method to be advanced for adoption as an AOAC Final Action method. Conclusions: The method described in AOAC 2016.14 is suitable for the determination of fructans in infant formula and adult nutritionals.